Reforming Indonesia's Criminal Prosecution System: The Challenge of Integrating Modern Evidence in Addressing Transnational Crime - I Ketut Dody Arta Kariawan; Abdul Majid; Nurini Aprilianda; Fachrizal Afandi; Uzodinma Yurriens Ezenduka (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2025)
Introduction: The development of transnational crime fundamentally requires efforts to update the criminal evidence system in Indonesia. This is because the characteristics of transnational crime are cross-border and are committed using technological advancements that are not yet covered or even regulated by positive law in Indonesia. Purposes of the Research: This research aims to analyze and propose reforms to the criminal justice system in Indonesia by integrating modern evidence in the face of transnational crime. Methods of the Research: This research uses a normative legal research method with a conceptual and legislative approach. Results Main Findings of the Research: The results of this study confirm that the urgency of reforming the criminal evidence system in Indonesia is a highly pressing and crucial matter for addressing the complexities of transnational crime, particularly money laundering, which demands more adaptive and effective methods of proof than the current provisions in the Criminal Procedure Code. More detailed updates to the Criminal Procedure Code regarding evidence, particularly digital and cross-border evidence, along with strengthened international cooperation and increased capacity of law enforcement officers in digital forensics and handling transnational crimes, are important steps. The reform of Indonesia's criminal evidence system, which integrates modern evidence tools to combat transnational crimes, requires a substantive revision of Article 184 of the Criminal Procedure Code to explicitly include electronic evidence as a category of valid evidence. Therefore, more detailed updates to the Criminal Procedure Code and the Anti-Money Laundering Law regarding evidence, particularly digital and cross-border evidence, along with strengthened international cooperation and increased capacity of law enforcement officers in digital forensics and handling transnational crimes, are important steps to strengthen the effectiveness of law enforcement against transnational crimes.